2021
DOI: 10.1007/s12291-021-00961-6
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements as Immunoregulators in SARS-CoV-2 and Other Viral Infections

Abstract: Nutritional deficiency is associated with impaired immunity and increased susceptibility to infections. The complex interactions of trace elements with the macromolecules trigger the effective immune response against the viral diseases. The outcome of various viral infections along with susceptibility is affected by trace elements such as zinc, selenium, iron, copper, etc. due to their immuno-modulatory effects. Available electronic databases have been comprehensively searched for articles published with full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 95 publications
(88 reference statements)
0
42
1
2
Order By: Relevance
“…Further, the zinc deficiency also results in lymphoid atrophy and decreased T cell immunity. So, any imbalance of Zn also adversely affects immune functions [26]. In this study, serum zinc levels were found to be significantly decreased in the severe group when compared to mild, moderate and controls.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Further, the zinc deficiency also results in lymphoid atrophy and decreased T cell immunity. So, any imbalance of Zn also adversely affects immune functions [26]. In this study, serum zinc levels were found to be significantly decreased in the severe group when compared to mild, moderate and controls.…”
Section: Discussionmentioning
confidence: 44%
“…In vitro studies showed that SARS-CoV-2 viral spike protein interacts with ACE2 receptor, which is a zinc-dependent peptidyl dipeptide hydrolase. So, any imbalance of Zn adversely affects immune functions [26,27]. Previous studies also reported that a decrease in zinc levels supports the ACE2 to SARS-CoV-2 spike protein and an increase will inhibit the ACE2 expression resulting in reduced viral interaction [28].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, in this study, the probability of finding leukocytosis (OR 8) in patients with abnormal serum Cu was higher than those with normal Cu levels. Copper plays a crucial role in the development, maturation, and proper functioning of the immune system [94]. The maturing immune system relies on Cu and Zn [95], especially for antibody production (both Cu and Zn), function of neutrophils and monocytes (Cu) [96], and the viability, proliferation, and differentiation of cells of both the innate and adaptive immune system (Zn), as well as for the maintenance of skin and mucosal barriers (Zn) [95,96].…”
Section: Blood Analysis and Inflammatory Responsementioning
confidence: 99%
“…Previous studies have shown that micronutrient balance is essential for enhancing immune response and improving antiviral function [29]. Micronutrients, such as selenium and iron, have immunomodulatory functions and can influence susceptibility to various viral infections [30]. Selenium is essential for the proliferation and differentiation of immune cells [16].…”
Section: Discussionmentioning
confidence: 99%